Inmigrant labor: policies, civil rights, violence and the labor market. El Ejido (Almería, Spain) - Martínez Veiga, Ubaldo (ENDOXA, 2002)
An attempt will be made to inter-relate the three fundamental elements needed to analyse the situation in El Ejido. The first is the construction and invention of a market for temporary labour where in reality the situation is one of permanent Jobs. The second is the effort made by the agricultural proprietors to completely eliminate the costs of reproduction of the immigrant labour forcé. The third is the presence there of brutal spatial segregation. These three elements are inserted into a political and economic context in which the reproduction of the labour forcé as well as the manpower management are supposed to be problems that the State should resolve, either through social assistance or laws «ad hoc» regarding foreigners which act as disciplinary measures with respect to the immigrant worker population.